Extracellular Histones Profiles of Pediatric H3K27-Altered Diffuse Midline Glioma - Buzova, Diana; Petrilli, Lucia Lisa; Frohlich, Jan; Tsoneva, Desislava K; Bianco, Salvatore Daniele; Braghini, Maria Rita; Alisi, Anna; Mastronuzzi, Angela; Cerveny, Jan; Mazza, Tommaso; Vinci, Maria; Vinciguerra, Manlio (Molecular diagnosis & therapy, 2025)
BACKGROUND: Diffuse midline glioma, H3 K27-altered (DMG) is a fatal tumour that arises in the midline structures of the brain. When located in the pons, it is more commonly referred to as diffuse intrinsic pontine glioma (DIPG). DMG/DIPG is usually diagnosed when children are < 10 years, and it has a median overall survival of < 12 months after diagnosis. Radiological imaging is still the gold standard for DIPG diagnosis while the use of biopsy procedures led to our knowledge on its biology, such as with the identification of the canonical histone H3K27M mutation. However, the need to improve survival encourages the development of non-invasive, fast and inexpensive assays on biofluids for optimizing molecular diagnoses in DMG/DIPG. Here, we propose a rapid, new, imaging and epigenetics-based approach to diagnose DMG/DIPG in the plasma of paediatric patients. METHODS: A total of 20 healthy children (mean age: 10.5 years) and 24 children diagnosed with DMG/DIPG (mean age: 8.5 years) were recruited. Individual histones (H2A, H2B, H3, H4, macroH2A1.1 and macroH2A1.2), histone dimers and nucleosomes were assayed in biofluids by means of a new advanced flow cytometry ImageStream(X)-adapted method. RESULTS: We report a significant increase in circulating histone dimers and tetramers (macroH2A1.1/H2B versus control: p value < 0.0001; macroH2A1.2/H2B versus control: p value < 0.0001; H2A/H2B versus control: p value < 0.0001; H3/H4 versus control: p value = 0.008; H2A/H2B/H3/H4 versus control: p value < 0.0001) and a significant downregulation of individual histones (H2B versus control: p value < 0.0001; H3 versus control: p value < 0.0001; H4 versus control: p value < 0.0001). Moreover, histones were also detectable in the cerebrospinal fluid (CSF) of patients with DMG/DIPG and in the supernatant of SF8628, OPBG-DIPG002 and OPBG-DIPG004 DMG/DIPG cell lines, with patterns mostly similar to each other, but distinct compared to blood plasma. CONCLUSIONS: In summary, we identified circulating histone signatures able to detect the presence of DMG/DIPG in biofluids of children, using a rapid and non-invasive ImageStream(X)-based imaging technology, which may improve diagnosis and benefit the patients.
Keywords: Biomarkers, Tumor; lidé; mladiství; nádorové biomarkery; gliom; Female; dítě; Mutation; Adolescent; Humans; Histones; mutace; histony; předškolní dítě; Diffuse Intrinsic Pontine Glioma; Brain Stem Neoplasms; Child, Preschool; nádory mozkového kmene; mužské pohlaví; difuzní intrinsický pontinní gliom; epigeneze genetická; Epigenesis, Genetic; ženské pohlaví; Male; Child; Glioma